Molecular characterisation of hepatitis B virus isolated from human immunodeficiency virus-infected adults at various time points after the initiation of antiretroviral therapy - Singh, Lanish (My University, 2017)
Sub-Saharan Africa is a high endemicity region of both Hepatitis B Virus (HBV) and Human Immunodeficiency Virus (HIV) infection. There is a paucity of information in this highly endemic region on molecular evolution of HBV in HIV-infected individuals receiving longterm Lamivudine (Lam) therapy. This study aimed at characterizing the molecular evolution of HBV in HIV-infected black Southern Africans prior-to the initiation of a Lam- containing antiretroviral (ARV) drug regimen, and 3, 6, 12 and 18 months post-initiation. HBV viralloads were quantified using real-time PCR and used to determine the viral suppression in 39 participants from the Shongwe Hospital in rural Mpmualanga, Republic of South Africa. The study participants included 16 participants who were HBsAg+ and 23 HBsAg- at baseline. Of the HBsAg- participants, 19 remained negative throughout follow-up these were defined as the HBsAg- group. The remaining 20 participants were HBsAg+ at baseline and/or at one time-point during follow-up, are referred to as the HBsAg+ group, nine were HBsAg+ throughout the study. Seven participants sero-converted to HBsAg- at a median of 4.2 months, two participants gained the HBsAg at 18.3 months. Two participants were HBsAgat baseline, thereafter became sero-positive but had retro-converted to HBsAg- by last timepoint. A significant finding between these two HBsAg serological groups, was a higher viral suppression achieved in the HBsAg- group -100%, with the HBsAg+ group achieving 13.54% HBV suppression (p = 0.01). HBV was fully suppressed in ten participants, with no suppression found in the remaining participants 29, of which 10 experienced a virologic breakthrough (VBT). HBsAg-negativity was a predictor of viral suppression, with ten HBsAg-negative participants achieving full suppression of HBV (p = 0.01). The NS VBT+ group had a significantly higher percentage of viral suppression, 51,90%, compared to the NS VBT- group 14,35%, despite the VBT events (p = 0.03). Biochemical analysis revealed that baseline alanine transferase (ALT) levels were significantly lower in the full suppression (FS) group indicating that lower ALT levels are a predicator of viral suppression (p = 0.02). Participants in the FS group had significantly lower ALT levels (15.5) at baseline compared to the NS group (35) (p=0.02). Another finding of the study was that only participants belonging to the HBsAg-negative group were able to clear the HBV virus whereas HBsAg positivity at any time point precluded clearance of HBV DNA. The Basal Core Promotor/PreCore (BCP/PreC) and complete surface (S) regions were amplified and sequenced to genotype HBV isolated from this cohort, as well as find detection or immune escape mutations. The majority of HBV isolates belonged to subgenotype A1, with the exception of two baseline isolates that belonged to genotype E and subgenotype D3, respectively. Various mutations were found in the 61 BCP/PreC region sequences (T1753C, A1762T G1764A, Kozak sequence, G1862T, G1896A) that could account for the high prevalence of HBeAg-negative infections observed at the various time-points. These mutations can lead to the down regulation of PreC mRNA transcription or translation, and/or affect post-translational modification of HBeAg. Amplification of the complete S-region and overlapping Polymerase regions yielded 47 sequences. Twenty-three of these sequences were from baseline samples, and the remaining from follow-up time-points. PreS deletions involved in the development of HCC were found in two follow-up isolates. These deletions, and other immune or detection escape mutations found in the S region, may contribute to the HBsAg negativity found in this study. In conclusion ALT levels and HBsAg status at baseline were predictors of the outcome of HBV suppression in response to anti-retroviral therapy. This study adds to the limited information available on the molecular changes observed in HBV isolates in HIV-infected South Africans under selection pressure from Lam.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine November 2017
Keywords: Hepatitis B virus; HIV; Antiretroviral Therapy